2022
DOI: 10.3390/su14137577
|View full text |Cite
|
Sign up to set email alerts
|

Green Mining Strategy Selection via an Integrated SWOT-PEST Analysis and Fuzzy AHP-MARCOS Approach

Abstract: Deciding on an appropriate development strategy is one of the most crucial aspects of the mining industry’s green transition. This research introduces a novel integrated decision support model that can be applied to analyze various environmental factors and determine development strategies. In this study, a strengths, weaknesses, opportunities, and threats (SWOT) analysis is employed from multiple perspectives, including political, economic, social, and technological (PEST), to assess the internal and external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The last step of determining the best alternative is to calculate the overall value of the priority alternative solutions as shown in the following table . Table 8. Overall value priority alternative solution From the table above, it can be concluded that the highest weight of the overall value of all criteria is the partnership program, this result is obtained because of the views of various stakeholders who want to preserve the mining activity but still want to preserve the existing environment, this is in line with other studies that use the AHP method to see green mines (Wu et al, 2022).…”
Section: Table 7priority Towards Repairing Environmental Damagesupporting
confidence: 78%
“…The last step of determining the best alternative is to calculate the overall value of the priority alternative solutions as shown in the following table . Table 8. Overall value priority alternative solution From the table above, it can be concluded that the highest weight of the overall value of all criteria is the partnership program, this result is obtained because of the views of various stakeholders who want to preserve the mining activity but still want to preserve the existing environment, this is in line with other studies that use the AHP method to see green mines (Wu et al, 2022).…”
Section: Table 7priority Towards Repairing Environmental Damagesupporting
confidence: 78%
“…The results of research conducted using in-depth interviews, obtained several analyzes related to external and internal analysis methods to inform strategic decisions that are in line with research objectives and the current environment of the subject under study, enabling maximization of strengths, mitigation of weaknesses, exploitation. opportunities, and mitigating threats [6]. 1.…”
Section: Results and Discussion A Analysismentioning
confidence: 99%
“…SWOT analysis highlights the 'strengths', 'weaknesses', opportunities, and 'threats' involved in an organization, plan, project, person, or business activity. SWOT analysis is also a tool used for strategic planning and management strategy, which can be used effectively to build organizational and competitive strategy [22][23][24]. S (strengths) and W (weaknesses) are internal factors, and O (opportunities) and T (threats) are external factors.…”
Section: Methodsmentioning
confidence: 99%